Symbolic number of seven in kazakh literature (Eurasian Journal of Philology Science and Education, 2019)
The article considers the peculiarity of the symbolism of the number seven in the Kazakh literature.The works of Kazakh poets of the 19th and 20-th centuries are analyzed.Since ancient times, numbers have played an important role in the life of many peoples. Somenumbers had a deep meaning, sacredness, some magical power was attributed to them. Kazakh culturewas no exception. Among the frequently used numbers, the number seven plays a special role amongthe Kazakh people.The symbolism of the number seven in the Kazakh culture and literature reflects the traditional ideasof the Kazakhs about the world order. Seven is a sacred and fundamental concept related to integrity,completeness.In the works of Kazakh poets, seven also most often symbolize the completeness, the connectionbetween life and death, all phenomena, the genealogy, the spiritual connection with the ancestors, theethno-cultural memory of the people.Seven is a key word in the works of Shakarim, M. Makatayev, K. Murzaliyev, M. Shahanov. Seven iscombined with many words and concepts and has rich symbolism. This is the dimension of everythingthat exists, the concept of happiness and the meaning of earthly life